ISLAMIC PSYCHOLOGY OF ABŪ ZAYD AL-BALKHĪ AS A FRAMEWORK FOR OVERCOMING DEPRESSION, STRESS, AND SOCIAL ISOLATION - Arroisi, Jarman; Muhammad, Allan (Kanz Philosophia: A Journal for Islamic Philosophy and Mysticism, 2025)
The contemporary global mental health crisis—marked by rising rates of depression, chronic stress, and social disconnection—calls for approaches that integrate biological, psychological, social, and spiritual dimensions of human well-being. This study revisits the biopsychological framework of Abū Zayd al-Balkhī (850–934 CE), articulated in Maṣāliḥ al-Abdān wa al-Anfus, to assess its relevance for contemporary challenges. Drawing on a qualitative literature review and comparative analysis, the research highlights how al-Balkhī’s classifications of ḥuzn (sorrow/depression), waswasah (obsessive rumination), and faza‘ (panic) bear conceptual parallels to modern diagnostic categories, while his therapeutic strategies—including cognitive reflection, behavioral regulation, spiritual devotion, and social companionship—demonstrate an integrative orientation that resonates with, but is not reducible to, contemporary therapies such as Cognitive Behavioral Therapy (CBT), positive psychology, and mindfulness. The paper also underscores the epistemological and clinical challenges of adapting al-Balkhī’s framework today. These include differences in ontology and methodology, terminological disparities with DSM/ICD systems, lack of empirical validation, and the risk of decontextualization if his thought is applied without critical adaptation. Nevertheless, the study argues that al-Balkhī’s synthesis of Qur’anic theology, Greco-Arabic medicine, and philosophical rationalism offers valuable resources for developing culturally resonant and ethically grounded models of care. His legacy can enrich mental health discourse in Muslim-majority contexts and pluralistic societies alike, provided it is engaged reflexively, critically, and in dialogue with contemporary clinical evidence.